On variational approach to economic equilibrium — type problem - Naniewicz, Zdzisław; Nockowska, Magdalena (Annales Mathematicae Silesianae, 2006)
The paper deals with an optimization problem in which minima of a finite collection of objective functions satisfy some unilateral constraints and are linked together by a certain subdifferential law. The governing relations are variational inequalities defined on a nonconvex feasible set. By reducing the problem to a variational inequality involving nonmonotone multivalued mapping defined over a nonnegative orthant, the existence of solutions is established under the assumption that constrained functions are positive homogeneous of degree at most one.